PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS ASSISTED INDIVIDUALIZATION (TAI) DISERTAI PORTOFOLIO DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS VII SMPN 3 SUNGAI LIMAU KABUPATEN PADANG PARIAMAN - hamda, Winda pratiwi; Rahmi, Rahmi; Anggraini, Villia (STKIP PGRI Sumbar, 2013)
This research was motivated by the low of studentsâ achievement, it cause the less optimal of students in response to the learning, Â the students just keep silent when the teacher asked, and just accept what the teacher teaches. This research is Â aims to determine whether the results of students mathematics in learning with implementing of cooperative learning type Team Assisted Individualization with portfolio was better than the result of conventional learning mathematics of Â grade students VII SMPN 3 Sungai Limau Kabupaten Padang Pariaman. type of this research is experimental research by using the random subject. Based on the value of learning outcomes that uses the type Team Assisted Individualization portfolio is accompanied by increase of the data analysis showed that the average value of the experimental class was 78.70 higher than the control class 65.67. It can be concluded that, the studentsâ result by applying the type of Team Assisted Individualization with portfolio is better than conventional learning outcomes.